CT virtual intravascular endoscopy assessment of coronary artery plaques:A preliminary study - Sun, Zhonghua; Jacobus D.; Nugrohob, J.; Adipranotob, J. (Elsevier Ireland Ltd, 2009)
Purpose: The purpose of this study was to investigate the potential value of CT virtual intravascular endoscopy (VIE) in the visualization and assessment of coronary plaques in patients suspected of coronary artery disease.Materials and Methods: 20 (13 men, 7 women, mean age 54 years) consecutive patients with suspected coronary artery disease undergoing 64-slice CT angiography were included in the study. Four main coronary artery branches were assessed with regard to the presence of coronary plaques based on 2D axial, multiplanar reformation, 3D volume rendering and VIE visualizations. The coronary plaques were characterized into calcified, noncalcified and mixed plaques. The intraluminal appearances of these coronary plaques were demonstrated with VIE images and correlated with 2D and 3D images to determine the diagnostic value of VIE for assessment of the plaques.Results: VIE was able to identify and demonstrate the intraluminal appearances of coronary plaques in 18 patients involving 32 coronary artery branches which was shown as an irregularly intraluminal protruding sign in extensively calcified plaques and smooth protruding appearance in noncalcified or focally calcifed plaques. An irregular intraluminal apearance was also noticed in the presence of mixed plaques due to variable components with different CT attenuation contained within the plaques. VIE accurately confirmed the degree of coronary stenosis or occlusion despite presence of heavy calcification.Conclusion: VIE could be used as a complementary tool to conventional CT visualizations for analysis of luminal changes and assessment of disease extent caused by the coronary plaques.